Authentication Of Transaction Process In E-marketplace Based On Blockchain ??technology - Adiyanto, Adiyanto; Febrianto, Rizki (Pandawan, 2020)
The very rapid development of technology is currently causing a revolution digital and the era of technological disruption or known as industry 4.0. with the presence of this 4.0 industry occurred computer growth and record-keeping automation all fields. This allows every human job to be replaced by robots, causing changes in the trading system that was done directly can now be done online or also known as Marketplace. With trade conducted through the internet, the transaction process is carried out on a traditional or directly, is now turning to the digital transaction process through Internet. The transaction process carried out digitally requires accuracy, security, and good trust between seller and buyer. Management Customer Relations or better known as Customer Relationship Management (CRM) is one model that can be used in maintaining the relationship between the customer and the company. Blockchain technology is technology that is able to maintain the transaction process, to maintain management efficiency identity, tracking system implementation, identifying product authenticity, and synchronization recording data to all parties, is expected to increase trust and the relationship between the customer and the seller.